Aktualność homilii Orygenesa we współczesnym przepowiadaniu - Dyk, Stanisław (Vox Patrum, 2020)
The goal of the article is to show the extent to which Origen’s homilies can be used as a model and inspiration for today’s homilies. It focuses on the formal aspects of Origen’s preaching, who was regarded as a master for spiritual interpretation of the Holy Scriptures and a “father” of the exegetical homily. His method of working with the sacred text and communicating its saving message was compared with the instructions for homilies contained in contemporary church documents and theological reflections. Our considerations lead to the following conclusions: Origen’s homilies are still current in terms of their Christological focus; the spiritual interpretation of the Bible is combined with openness to the light of the Holy Spirit; and he uses a direct, simple and dialogical style of preaching. On the other hand, objections are raised due to the lack of reference to the everyday life problems of his audience; Origen’s homilies are not acceptable today with regard to their composition because he elucidates the sacred text verse by verse.